2017
DOI: 10.1002/adfm.201704083
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Ion (Fe, V, Co, and Ni)‐Doped MnO2 Ultrathin Nanosheets Supported on Carbon Fiber Paper for the Oxygen Evolution Reaction

Abstract: Manganese dioxides (MnO2) are considered one of the most attractive materials as an oxygen evolution reaction (OER) electrode due to its low cost, natural abundance, easy synthesis, and environmental friendliness. Here, metal‐ion (Fe, V, Co, and Ni)‐doped MnO2 ultrathin nanosheets electrodeposited on carbon fiber paper (CFP) are fabricated using a facile anodic co‐electrodeposition method. A high density of nanoclusters is observed on the surface of the carbon fibers consisting of doped MnO2 ultrathin nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
126
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(144 citation statements)
references
References 54 publications
7
126
0
Order By: Relevance
“…XRD analysis (Figure 1a) showed that they can all be assigned to layered Birnessite-type δ-MnO 2 ( Small 2020, 16,1905223 Scheme 1. Schematic illustration of the synthetic process of Ni-Fe-K 0.23 MnO 2 CNFs-300.…”
Section: Resultsmentioning
confidence: 99%
“…XRD analysis (Figure 1a) showed that they can all be assigned to layered Birnessite-type δ-MnO 2 ( Small 2020, 16,1905223 Scheme 1. Schematic illustration of the synthetic process of Ni-Fe-K 0.23 MnO 2 CNFs-300.…”
Section: Resultsmentioning
confidence: 99%
“…The superior catalytic performance should be attributed to the unique nanosheet-based microsphere structure and the synergistic effect between Ni and V, which is consistent with the previous reports. [43][44][45][46] The special 3D structure provides a large surface area, thus increasing the number of active sites. When combining with NF, the material has better electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[22,23] For example, density functional theory (DFT) calculations show that the sites where Se atoms are at the edges of transition metal selenides are HER active sites. [29][30][31] In this case, it is expected that Exploring highly efficient and low-cost electrocatalysts for electrochemical water splitting is of importance for the conversion of intermediate energy. Indeed, incorporation of heterogeneous metal atoms can induce atomic distortions due to strain and result in additional exposed active sites.…”
mentioning
confidence: 99%
“…[24] Furthermore, it has been shown that the heterogeneous metal atoms doping could optimize the hydrogen adsorption kinetic energy and improve the HER catalytic activity in comparison to monometallic ones. [29][30][31] In this case, it is expected that Exploring highly efficient and low-cost electrocatalysts for electrochemical water splitting is of importance for the conversion of intermediate energy. Moreover, the electronic interaction between each element in mono-cation-doped electrocatalysts has been always ignored.…”
mentioning
confidence: 99%